2006
DOI: 10.1305/ndjfl/1168352663
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Abstract Algebraic Logic: More on Protoalgebraicity

Abstract: Protoalgebraic logics are characterized by the monotonicity of the Leibniz operator on their theory lattices and are at the lower end of the Leibniz hierarchy of abstract algebraic logic. They have been shown to be the most primitive among those logics with a strong enough algebraic character to be amenable to algebraic study techniques. Protoalgebraic π-institutions were introduced recently as an analog of protoalgebraic sentential logics with the goal of extending the Leibniz hierarchy from the sentential fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…This characterization fills in a gap that was left open in the development of the theory of prealgebraicity and protoalgebraicity of [18]. As another important consequence of Theorem 3.2, it is shown that, in the context of N -protoalgebraic π-institutions, the N -Leibniz theory family T (N ) corresponding to a given theory family T , defined in a way analogous to the N -Leibniz theory system T N corresponding to a given theory system T in [20], is an N -Leibniz theory system. Therefore all N -Leibniz theory families are N -Leibniz theory systems and the theory of [20] covers these families in their full generality.…”
Section: Important Consequencesmentioning
confidence: 95%
See 3 more Smart Citations
“…This characterization fills in a gap that was left open in the development of the theory of prealgebraicity and protoalgebraicity of [18]. As another important consequence of Theorem 3.2, it is shown that, in the context of N -protoalgebraic π-institutions, the N -Leibniz theory family T (N ) corresponding to a given theory family T , defined in a way analogous to the N -Leibniz theory system T N corresponding to a given theory system T in [20], is an N -Leibniz theory system. Therefore all N -Leibniz theory families are N -Leibniz theory systems and the theory of [20] covers these families in their full generality.…”
Section: Important Consequencesmentioning
confidence: 95%
“…This result has two very important consequences for the theory of categorical abstract algebraic logic. On the one hand, it provides a characterization of the class of N -protoalgebraic π-institutions inside the class of N -prealgebraic π-institutions, as introduced in [18], and, on the other hand, it yields the interesting property that the N -Leibniz theory family T (N ) corresponding to a given theory family T of an N -protoalgebraic π-institution I is an N -Leibniz theory system, as introduced in [20].…”
Section: Largest Theory System In a Theory Familymentioning
confidence: 99%
See 2 more Smart Citations
“…In a way very similar to the way an N -parameterized equivalence system behaves with respect to the N -Leibniz operator on π-institutions (see, e. g., [24,Proposition 4.1]), the analytical relation system E(T ) on SEN determined by E and T has the property that, if it is reflexive, then it contains the N -Suszko congruence system of T . P r o o f. In fact, suppose that Σ ∈ |Sign|, ϕ, ψ ∈ SEN(Σ) such that ϕ, ψ ∈ Θ N Σ (T ).…”
Section: Determinator Systems For the Suszko Operatormentioning
confidence: 97%